Standardized Assessment of TKA Equivalent for Junior High School Students - Nur Roudlotul Jannah; Cholis Sa'dijah; Tjang Daniel Chandra (PRISMA, 2026)
This research aims to develop a mathematical assessment instrument equivalent to the Academic Ability Test (TKA) for junior high school students who have good measurement quality. This research uses a Research and Development (R&D) approach by adapting the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The instrument developed consists of three question items that are arranged based on the TKA preparation grid with emphasis on mathematical reasoning skills, problem solving, and critical thinking. The research subjects consisted of expert validators including experts in mathematics and educational evaluation experts, as well as 80 junior high school students as respondents to the instrument trial. The data collection technique is carried out through expert validation sheets and tests of student work. Data analysis was carried out descriptively to assess the feasibility of the instrument's contents, while empirical validity was analyzed using corrected item-total correlation and reliability was analyzed using Cronbach's Alpha coefficient with the help of IBM SPSS Statistics software. The results showed that all question items had a corrected item-total correlation value that was greater than the r-value of the table (0.220) so that it was declared valid. In addition, the results of the reliability test showed a Cronbach's Alpha value of 0.953 which was in the very high category. These findings show that the assessment instruments developed have a very good level of validity and reliability so that they are suitable for use as an alternative assessment to measure the academic ability of junior high school students that are in line with TKA standards.